POSTMODERNISM AND THE RELATIONSHIP OF THE IMPLEMENTATION GOOD CORPORATE GOVERNANCE - Syahrian Syahrian (Dinasti Publisher, 2019)
Postmodernism, a reality that is beginning to have a strong influence on the lives of individuals and groups, is no exception in the management of organizations, particularly good corporate governance (GCG). This understanding has led to pessimism and apathy toward the increasingly uncontrollable passion of life, as a result of thoughts that no longer believe in absolute truth and objective and rational standards. This paper further reveals the implications of postmodernism on ethics, proxy war, and optimizing the application of GCG in government organizations. The results of the in-depth study concluded that postmodernization was entrenched in the lives of both individuals and groups, doing what was right in their own view (group), reduced trust in community diversity, pluralism, relativism, information overload, high mobility, identity confusion, consumerism and etc. Ethics has been eliminated and the proxy war is out of control. Proxy war as an arm of a country that seeks to get its strategic interests in a particular country. Proxy war has taken place in various forms, especially in Indonesia, such as ethics in the use of the internet.